Effect of Phosphate Addition and Exposure of Micro Waves on Comparatives Ca/F in Gipsum Waste: Preliminary Study of Hydroxyappatite Synthesis (HAp) from Ceramics Gypsum Industry Waste - Dewantoro Dewantoro; Margareta Novian Cahyanti; Sri Hartini (Jurnal Kimia Sains dan Aplikasi, 2018)
This study aims to conduct an initial study of hydroxyapatite synthesis from ceramic gypsum waste. The parameters of the synthesis process carried out were variations in the time of the hydrothermal process namely 10, 20, 30, 40 and 50 minutes. The time variation was studied to study the effect of time on the hydroxyapatite character of gypsum waste. The initial synthesis process was conducted by looking at the comparison of Phosphate and Calcium levels in gypsum. In this study the results of the highest Phosphate levels obtained were 0.607% in the 10th  minute, while the largest Calcium levels were obtained in the 30th minute which was 0.171%. The treatment in the 30th minute gave the most optimal difference in effect which was 0.413. FTIR results showed the emergence of hydroxyapatite peaks namely –OH, PO43- and Ca-O, as well as the increase in the intensity of the peak of gypsum powder before treatment and after treatment. While the XRD results strengthened the presence of hydroxyapatite in gypsum with the presence of high peaks at 2θ = 31.08°; 32.14° and 33.45° respectively which indicated the presence of hydroxyapatite. While the main impurities in the synthesized hydroxyapatite are carbonates identified from FTIR results.